Globalised Criminality, Local Crime Control and Prevention - Ferenc, Irc (Sociologija. Mintis ir veiksmas, 2007)
The study deals with some key-definitions in the field of crime prevention and control as security, risk, danger, public security, interior security, public order. Globalization as a group of unfinished changes in our risk society takes challenges for criminal policy. The essence of the new approach is that it tries to define the adequate reaction to the consequence of some harm depending on what consequences the harm entails in the short term and in the long term and depending also on what interventions are the most promising to help avoid these consequences in the future.